Rapid ELISA Assay for Plasma D-Dimer in the Diagnosis of Segmental and Subsegmental Pulmonary Embolism - Sijens, Paul E.; van Ingen, Huub E.; van Beek, Edwin J. R.; Berghout, Arie; Oudkerk, Matthijs (Thrombosis and Haemostasis, 2000)
Study objective To assess the accuracy of a rapid ELISA D-dimer assay for the exclusion of pulmonary embolism (PE) in patients suspected of PE, using pulmonary angiography alone as reference method rather than a diagnostic strategy including lung scintigraphy and leg vein ultrasonography. Methods In 342 patients who were examined by pulmonary angiography to diagnose or exclude PE, the accuracy of the quantitative rapid VIDAS D-dimer test for the exclusion of PE was evaluated retrospectively. D-dimer levels were assayed in frozen samples collected during the diagnostic work-up at the time of pulmonary angiography while on treatment with unfractionated heparin for 1-2 days. Results Mean plasma D-dimer concentrations were increased in patients with angiographic evidence of PE (P <0.0001). The sensitivity of D-dimer for segmental PE was 98%, its accuracy in excluding segmental PE was 99%, higher than the respective figures for subsegmental PE (76% and 94%; P <0.01, both). For both forms of PE combined the sensitivity was 90% and the negative predictive value 94%. Discussion The sensitivity and negative predictive values reported here, are low compared with previous studies using the same rapid ELISA D-dimer assay. This probably reflects an overlooking of mild cases of subsegmental PE in previous studies, although a reduction of D-dimer levels by the heparin pretreatment may have contributed to part of the discrepancy. Prospective studies are needed to clarify this issue.
Keywords: Pulmonary embolism; diagnosis; D-dimer; fibrinolysis; angiography